Environmental implications of the use of bio-cement treated recycled aggregate in concrete - Mistri, Abhijit; Dhami, Navdeep; Bhattacharyya, Sriman Kumar; Barai, Sudhirkumar V; Mukherjee, Abhijit; Biswas, Wahidul (2021)
Use of aggregates from recycled construction and demolition wastes in concretes alleviates the disposal problem and reduces the cost of concrete significantly. However, excessive water absorption, weak interfacial transition zone, and high porosity are its shortcomings. This study explores a bacterial cement and conventional cement slurry coating treatment on recycled coarse aggregates (RCA) for overcoming these shortcomings. In the first method, microbial carbonate precipitation (MCP) through bio-mineralization treatment has been utilized. Four different concretes were made using both control and treated aggregates. Once the performance of these concrete mixes was found adequate, a life cycle assessment was conducted using ISO14040–44 guideline to determine their environmental impacts. The experimental results confirmed that concrete with MCP treated aggregate offered better material performance than the untreated recycled aggregate based concrete mixes and possessed similar properties as natural aggregate concrete. While MCP process avoided the use of energy intensive cement, this research discovers that concrete with MCP treated aggregates was found to produce marginally higher environmental impacts than other concrete mixes mainly due to additional emissions associated with the bio-cement treatment of RCA. Further environmental mitigation strategies for concrete with MCP treated aggregates has considered to improve its environmental performance in terms of global warming impact and cumulative energy demand. This study demonstrates that the use of 100% RCA delivers significant environmental benefits in terms of ecological footprints, land conservation and biodiversity in a densely populated region like India.